Isothermal signal amplification-mediated nanozyme capture on DNA tetrahedra for ultrasensitive amperometric immunoassay of Epstein–Barr virus latent membrane protein 1 - Liao, Lin; Li, Zhaoxiong; Liu, Zhanhong; Qiu, Bin; Guo, Wangyuan (Frontiers in Chemistry, 2025)
The overexpression of latent membrane protein 1 (LMP-1), a key oncoprotein encoded by the Epstein-Barr virus (EBV), is closely associated with the development and progression of nasopharyngeal carcinoma (NPC), making it a valuable biomarker for early diagnosis and prognosis. Herein, we report a highly sensitive amperometric immunoassay method for LMP-1 detection based on the strand displacement amplification (SDA)-mediated capture of nanozyme on a DNA tetrahedron (TDN)-modified electrode. In detail, a sandwich immunoassay was carried out on a microplate, followed by sequential capture of streptavidin and biotin-labeled SP-HP, which then initiated SDA in the presence of a nicking enzyme and DNA polymerase. The resulting trigger DNA hybridized with TDN-anchored hairpin probes, exposing terminal digoxin moieties that captured anti-digoxin antibody modified AuPt alloy nanozymes. The nanozymes catalyzed the oxidation of TMB in the presence of H2O2, generating electroactive oxidized products that were subsequently reduced at the electrode to yield a measurable current signal. The integration of TDNs, SDA, and AuPt nanozymes significantly enhanced sensitivity, achieving a detection limit as low as 47 fg mL-1 and a wide linear range (0.1–1,500 pg mL-1). The developed method also demonstrated excellent specificity, reproducibility, and applicability in spiked biological samples. This work presents a promising strategy for ultrasensitive and specific detection of EBV-related proteins and expands the utility of nanozyme-based electrochemical immunoassays for clinical diagnostics.